Optimization of Different Leguminous Extenders on Spent Breeder Hen Meat Balls - Indumathi, J.; Babu, A. Jagadeesh; Reddy, B. Obula (Journal of Meat Science, 2015)
Spent breeder hen meat balls using different types of flours were analyzed for their physico-chemical and sensory properties by repeated trials. Three different extenders viz. black gram flour, green gram flour and red gram flour at the level of 10% were used to formulate the meat balls. Among formulations spent breeder hen meat balls incorporated with red gram flour had moderately higher values of emulsion stability, water holding capacity, moisture retention, crude fat and fiber values compared to all other formulations though it was not significant (p>0.05) between other flour extended formulations, but there was significant difference (p
Keywords: Breeder hen; Meat balls; Leguminous extender; Process optimization